2020
DOI: 10.3847/1538-4357/ab6321
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Toroidal Flux of Preexisting Flux Ropes of Coronal Mass Ejections

Abstract: In past decades, much progress has been achieved on the origin and evolution of coronal mass ejections (CMEs). In-situ observations of the counterparts of CMEs, especially magnetic clouds (MCs) near the Earth, have provided measurements of the structure and total flux of CME flux ropes. However, it has been difficult to measure these properties in the erupting CME flux rope, in particular in the pre-existing flux rope. In this work, we propose a model to estimate the toroidal flux of the preexisting flux rope … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 92 publications
2
6
0
Order By: Relevance
“…The lower estimate for the toroidal flux from the dimming method than the estimate for the poloidal flux from the flare ribbon method found in this study is in agreement with the result obtained from the statistical study by Sindhuja and Gopalswamy (2020). Some studies have however also indicated a significant increase in toroidal flux due to flare reconnection during the CME eruption (e.g., Xing et al, 2020). The temporal evolution of axial/poloidal fluxes and twist in flux ropes, and determination of those from the simulation data, are complicated research questions that require more extensive future investigations.…”
Section: Summary and Discussionsupporting
confidence: 89%
“…The lower estimate for the toroidal flux from the dimming method than the estimate for the poloidal flux from the flare ribbon method found in this study is in agreement with the result obtained from the statistical study by Sindhuja and Gopalswamy (2020). Some studies have however also indicated a significant increase in toroidal flux due to flare reconnection during the CME eruption (e.g., Xing et al, 2020). The temporal evolution of axial/poloidal fluxes and twist in flux ropes, and determination of those from the simulation data, are complicated research questions that require more extensive future investigations.…”
Section: Summary and Discussionsupporting
confidence: 89%
“…It was found that most (80%) of the MCs have a twist larger than 1.25 turns per AU, and some of the MCs have a twist larger than 10 turns per AU. Two factors are attributed to the high twist, one is the initial flux in the source region before eruption (Xing et al 2020), and the other is magnetic reconnection during eruption, which converts the ambient magnetic field to the MFR flux (Longcope & Beveridge 2007;Qiu 2009;Aulanier et al 2012;Wang et al 2017). According to our results, quiescent filaments are generally more twisted than active-region filaments before eruption.…”
Section: Origin Of Twists In Interplanetary Magnetic Cloudssupporting
confidence: 52%
“…Since the distribution of the coronal and the photospheric magnetic fields play a dominant role in triggering coronal flux rope eruptions (Yeates 2014;Yang et al 2018;Thalmann et al 2019;Xing et al 2020), the influence of flux feeding processes on the major rope system should be sensitive to the scale of the magnetic field strength in the small rope. The magnetic parameters of the resultant flux ropes after the flux feeding processes with different C E are tabulated in Table 1.…”
Section: Initiation Of Eruptionsmentioning
confidence: 99%